ABCD3-I and ABCD2 Scores in a TIA Population with Low Stroke Risk. (25th February 2021) - Ildstad, Fredrik; Ellekjær, Hanne; Wethal, Torgeir; Lydersen, Stian; Fjærtoft, Hild; Indredavik, Bent
Abstract : Objectives . We aimed to evaluate the ABCD3-I score and compare it with the ABCD2 score in short- (1 week) and long-term (3 months; 1 year) stroke risk prediction in our post-TIA stroke risk study, MIDNOR TIA. Materials and Methods . We performed a prospective, multicenter study in Central Norway from 2012 to 2015, enrolling 577 patients with TIA. In a subset of patients with complete data for both scores (n = 305 ), we calculated the AUC statistics of the ABCD3-I score and compared this with the ABCD2 score. A telephone follow-up and registry data were used for assessing stroke occurrence. Results . Within 1 week, 3 months, and 1 year, 1.0% (n = 3 ), 3.3% (n = 10 ), and 5.2% (n = 16 ) experienced a stroke, respectively. The AUCs for the ABCD3-I score were 0.72 (95% CI, 0.54 to 0.89) at 1 week, 0.66 (95% CI, 0.53 to 0.80) at 3 months, and 0.68 (0.95% CI, 0.56 to 0.79) at 1 year. The corresponding AUCs for the ABCD2 score were 0.55 (95% CI, 0.24 to 0.86), 0.55 (95% CI, 0.42 to 0.68), and 0.63 (95% CI, 0.50 to 0.76). Conclusions . The ABCD3-I score had limited value in a short-term prediction of subsequent stroke after TIA and did not reliably discriminate between low- and high-risk patients in a long-term follow-up. The ABCD2 score did not predict subsequent stroke accurately at any time point. Since there is a generally lower stroke risk after TIA during the last years, the benefit of these clinical risk scores and their role in TIA management seems limited. Clinical Trial Registration . This trial is registered with NCT02038725 (retrospectively registered, January 16, 2014).